Mask RCNN Methods for Eyes Modelling - Hidayat, Rahmat; Hendrick; Riandini; Wang , Zhi-Hao; Gwo-Jiun , Horng (International Journal of Data Science, 2021)
Object detection is one of Deep Learning section in Computer Vision. The application of computer vision is divided into image classification and object detection. Object detection have target to find specific object from an image. The application of object detection for security are face recognition, and face detection. Face detection have been developed for medical application to identify emotion from faces. In this research, we proposed an eye modelling by using Mask RCNN. The eye model was applied in real time detection combined with OpenCV. The dataset was created from online dataset and image from webcam. The model was trained with 4 epochs and 131 iterations. The final model was successfully detected eye from real-time application.